ANALISIS SWOT PASAR MODAL SYARIAH SEBAGAI SUMBER PEMBIAYAAN DI INDONESIA - Basrowi Basrowi; Pertiwi Utami; Erike Anggraeni; Muhammad Nasor (el-Jizya: Jurnal Ekonomi Islam, 2020)
The purpose of this study is to provide a literature review of the problems currently faced by Islamic Capital Markets, given that Islamic capital market products have not been used significantly as a source of financing outside of Islamic Banks. Whereas the opportunity as an alternative source of funding is quite large, especially because of the potential of the majority of Indonesian Muslims. The method used in this study is the literature method based on the most up-to-date reading sources from books and journals. Data analysis methods used are SWOT analysis so that it is expected to find the right strategic solution for using the Islamic capital market as a source of financing outside the bank. The results of the analysis indicate that the use of Islamic capital market products has a positive force by continuously maintaining its existence. Its superiority is influenced by its activities which avoid Maghrib (Maysir, haram, usury and gharar). The impact is very significant on environmental empowerment or 'green economy' because it indirectly prohibits the practice of destroying natural resources for stakeholder actors. The disadvantage is the large number of human resources in the Islamic Capital Market who are unable to use sophisticated technology appropriately and optimally. Opportunities come from technological developments and increasing public financial literacy on the Islamic capital market. The obstacle is that there is a high risk due to external factors, namely political, economic, socio-cultural changes that must be watched because there is always no certainty about it.